Lymphocyte subpopulations in anaphylactoid purpura. Issue 7 (July 1980) - Musumeci, S; Sciotto, A; Rosalba, A; Volti, S L; Mollica, F
Abstract : The immunoglobulins, complement components C3 and C4, lymphocyte subpopulations, and K-cell activity were studied in 13 children with anaphylactoid purpura and in 12 children of the same ages who acted as controls. The children with anaphylactoid purpura had significantly lower T-cell counts, greater K-cell activity and IgM values, and lower C3 levels than the controls.